Durability of epoxy adhesives and carbon fibre reinforced polymer laminates used in strengthening systems: accelerated ageing versus natural ageing - Cruz, José Ricardo Loureiro (2021)
This work addresses the durability of structural epoxy adhesives and carbon fibre reinforced polymer (CFRP) laminates typically used in strengthening of existing reinforced concrete structures exposed to natural ageing. The experimental program included four natural (real) outdoor environments inducing ageing mainly caused by carbonation, freeze-thaw attack, elevated temperatures, and airborne chlorides from seawater. Moreover, a control (reference) environment (20 °C of temperature and 55% of relative humidity) and an environment involving water immersion of the materials under controlled temperature (20 °C of temperature) were also included in this investigation. The characterization involved the assessment of the physical, chemical and mechanical properties along a study period of up to two years. Furthermore, comparisons between the natural ageing tests developed in the scope of the present work and accelerated ageing tests existing in the literature were performed. Regarding to the epoxy adhesives, an increase in the glass transition temperature with the time was observed, while the tensile properties decreased, regardless of the outdoor environment. The CFRP laminates were marginally affected by the studied environments. Despite the remarkable dispersion of the results observed in the accelerated ageing tests for the period investigated, this testing protocol yielded higher mechanical degradation than under natural ageing.